POLA PENGELUARAN KONSUMSI RUMAHTANGGA TANI PENERIMA BANTUAN MODAL PRODUKSI TERNAK SAPI DI KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Tangkere, Christian; Umboh, S J.K; Manese, M A.V; Santa, N M (ZOOTEC, 2019)
THE PATTERN OF HOUSEHOLD FARMERS CONSUMPTION EXPENDITURE OF BENEFICIARIES OF CAPITAL ASSISTANCE FOR CATTLE PRODUCTION IN THE WESTERN TOMPASO DISTRICT OF MINAHASA REGENCY. Household farmers are one of the economic units that have a relationship with production and consumption decisions.  Assistance of livestock production capital obtained by household farmers allocated its use in the context of household consumption to maximize the utility or satisfaction of the household. This research aims to analyze the pattern of consumption expenditure on farmers households as a recipient of production capital assistance for livestock. The study used descriptive and quantitative analysis. The respondent of this research which is household farmer’s as one of the recipients of capital assistance that has been selling cows.  Patern of  household consumption expenditure by farmers as beneficiaries of capital assistance in the district of West Tompaso divided into: Food and Non-food consumption. Expenditure of food consumption differentiated two types which are expenditure of food consumption purchased and not purchased. The results showed that out of all three allocation of consumption expenditure is known that the allocation of food consumption expenditure of household farmers is divided in to the first; the largest purchased for fish production is 28.69 percent, second; the value expenditure of food consumption not purchased in food seasonings (29.94%), and the last one is the allocation of non-food consumption expenditure were on  clothing, footwear, and headgear (27.83%.) Keywords :Expenditure, consumption, households